KERJASAMA INDONESIA-FILIPINA DALAM MENCEGAH DAN MEMBERANTAS KEJAHATAN TRANSNASIONAL DI INDONESIA DAN FILIPINA KHUSUSNYA PERDAGANGAN NARKOBA/OBAT-OBATAN TERLARANG PERIODE 2011-2016 - Akhmad Qelbi El Hakim, - (2018)
Crime is a social phenomenon that has happened anywhere and anytime, the crime can be done by anyone also because the crime is due to the existence of gaps or opportunities that can be utilized by elements or parties that are not responsible. Transnational crimes occurring in Indonesia and the Philippines especially the trafficking of illegal drugs or drugs have occurred long enough between the two. Excessive use of drugs and without a prescription can cause abnormalities or diseases that attack the body. In conducting the prevention and eradication of drug trafficking in Indonesia and the Philippines, the two countries establish bilateral cooperation and establish programs that are expected to reduce the level of drug trafficking crimes that occur between them.